IoT-Based System of Monitoring Realtime Air Quality with MQ135 and Automatic Chicken Feeding - Dani Sasmoko; Reni Veliyanti; Rozi Azwar Pradana (University of Science and Computer Technology, 2022)
IoT technology is useful for chicken farming to control the condition of the farm concerning some problems such as odour, temperature fluctuations and feeding time system. This study used MQ135 to detect ammonia odour level, DHT11 to check room temperature, and RTC3231 to regulate feeding time. The data obtained from the sensor was sent by wemos to the fire base and MySQL to be read on android so that it can be monitored directly by the breeder. When the ammonia level is above normal it will turn on the odour fan. If DHT11 reaches the value above 300C, it will turn on the cooling fan, and turn on the heating light when the temperature is below 250C. As RTC3231 sets the time at 07.00 and 14.00, the chicken feeder will automatically open to feed the chickens according to the time set. Table 1 and 2 show that the experiment obtained a value of 100% working well. This study succeeded in monitoring environmental conditions through Android and executing automatic feeding at the predetermined time. Thus, it can be concluded that the use of IoT technology for monitoring and feeding system automation in chicken farms is highly recommended.